Investigation of local empty fruit bunch performance with adding cement bonded fiber - Gabriel Owen Sitor (2022)
The largest producers of agricultural waste came from the palm oil industry, particularly the oil palm empty fruit bunch (OPEFB). In Malaysia, palm oil mills have been reported to generate 2.4 million tons of OPDEFB annually, where most of it ditched as waste due to its bulky form and poor economic value. Improper disposal of the empty fruit bunches (EFB) leads to negative implication to the environment. Thus, integrating the local empty fruit bunch fiber into the cement will produced Fiber Reinforced Cement Composite (FRCC) which is enhanced in the mechanical properties. This study was carried out to investigate the performance of local empty fruit bunch with adding cement bonded fiber. The mechanical properties such as compressive strength and water absorption was evaluated through compression test and water absorption test. The percentage of fiber 1%, 2%, 3%, 4% and 5% were replaced with the sand weight in the 215mm x 96mm x 70mm brick specimens. The cement-sand mix ratio used was 1:4 and the cement-water ratio of 0.47. The result reveal that the optimum amount of EFB fiber content was 3% that yielded up to 50% of increased in strength development when it is compared to the control specimen. Besides, the study found out that excessive amount of EFB fiber content added in the cement composite will decrease the compressive strength and continue to increase water absorption.